2017
DOI: 10.1097/bcr.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Time Matters in Severe Frostbite

Abstract: Severe frostbite is associated with high levels of morbidity through loss of digits or limbs. The aim of this study was to examine the salvage rate following severe frostbite injury. Frostbite patients from 2006 to 2014 were identified in the prospectively maintained database at a single urban burn and trauma center. Patients with imaging demonstrating a lack of blood flow in limbs/digits were included in the analysis (N = 73). The Hennepin Frostbite Score was used to quantify frostbite injury and salvage. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The time to reach a clinical setting in order to receive advanced treatments (e.g., intravenous vasodilators or thrombolytic agents) was not considered in this study as none of the subjects received them. However, evidence suggests that reducing the time lapse before reaching an advanced medical post with possibilities of receiving more complex treatments such as thrombolytic factors and/or vasodilator iloprost in an adequate time frame may decrease the risk of amputation [12,23,24]. Nonetheless, more research is needed to evaluate the real impact of these therapies on frostbite sequelae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time to reach a clinical setting in order to receive advanced treatments (e.g., intravenous vasodilators or thrombolytic agents) was not considered in this study as none of the subjects received them. However, evidence suggests that reducing the time lapse before reaching an advanced medical post with possibilities of receiving more complex treatments such as thrombolytic factors and/or vasodilator iloprost in an adequate time frame may decrease the risk of amputation [12,23,24]. Nonetheless, more research is needed to evaluate the real impact of these therapies on frostbite sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to establish risk factors for frostbite [9,10,11], as well as risk factors for amputation once the patient has reached in-hospital care [12,13]. However, little is known of the possibility of reducing amputation rates and improving the quality of injury management in the field once frostbite has already occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal burns due to extreme cold were the subject of several articles, including the use of thrombolysis and a new scoring system, including an evaluation of the socioeconomic and cost and challenges of care provision for frostbite patients., 69,[241][242][243][244][245]…”
Section: Frostbitementioning
confidence: 99%
“…Studies have demonstrated a rapid loss of efficacy with delay of administration of thrombolytics. Nygaard et al showed that the time from rewarming to alteplase significantly impacted amputation rate, with each hour of delayed treatment leading to an additional 27% loss of tissue [ 15 ]. As per the aforementioned study, alteplase should ideally be initiated within 4 h of rewarming, with some benefits observed up to 12 h post-rewarming [ 15 ].…”
Section: Introductionmentioning
confidence: 99%